2016
DOI: 10.1002/art.39595
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Association of Rheumatoid Factor and Anti–Citrullinated Protein Antibody Positivity With Better Effectiveness of Abatacept: Results From the Pan‐European Registry Analysis

Abstract: Objective. To investigate the role of rheumatoid factor (RF) status and anti-citrullinated peptide antibody (ACPA) status as predictors of abatacept (ABA) effectiveness in patients with rheumatoid arthritis (RA).Methods. We conducted a pooled analysis of data from 9 observational RA registries in Europe (ARTIS [Sweden] [Switzerland]). Inclusion criteria were a diagnosis of RA, initiation of ABA treatment, and available information on RF and/or ACPA status. The primary end point was continuation of ABA treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
3
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(66 citation statements)
references
References 20 publications
7
51
3
5
Order By: Relevance
“…Double positivity for both RF and anti-CCP was associated with a greater likelihood of abatacept retention than either single positivity or double negativity, irrespective of treatment line. Real-world evidence from a pooled analysis of European RA registries has previously shown that RF and anti-CCP positivity were each strongly associated with improved retention of abatacept [34]. A positive association has also been demonstrated between abatacept retention and anti-CCP positivity in patients in clinical trials [35,36] and a registry study [37].…”
Section: Discussionmentioning
confidence: 94%
“…Double positivity for both RF and anti-CCP was associated with a greater likelihood of abatacept retention than either single positivity or double negativity, irrespective of treatment line. Real-world evidence from a pooled analysis of European RA registries has previously shown that RF and anti-CCP positivity were each strongly associated with improved retention of abatacept [34]. A positive association has also been demonstrated between abatacept retention and anti-CCP positivity in patients in clinical trials [35,36] and a registry study [37].…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, however, it is becoming increasingly clear that seropositivity for RF and/or ACPA does enhance response to rituximab (4042). Similarly, enhanced retention to abatacept in patients seropositive for RF and/or ACPA has also been observed in two independent cohorts (43, 44). Despite these observations, significant clinical challenges remain in predicting response to rituximab or abatacept with wide variability seen in response rates within the seropositive groups.…”
Section: Incorporating Imaging Into Clinical Prediction Models For Thsupporting
confidence: 55%
“…Ever since the discovery of the genetic association of RA to a subset of HLA-DR alleles (2), CD4 + T cells have been considered as classical effector cells in RA. Furthermore, the importance of CD4 + T cell effector functions in RA pathogenesis is corroborated both by therapeutic interventions affecting adaptive immune responses (3, 4) and by multiple studies of polyclonal T cell cytokine production (5, 6). The identification of RA-associated antibody responses to citrullinated proteins and the genetic link established between the presence of such autoantibodies and certain HLA class II molecules (7) has directed the investigation of novel autoantigens, and thereby promoted a renaissance in CD4 + T cells studies, as T helper cells would be assumed to govern IgG responses (8).…”
Section: Introductionmentioning
confidence: 97%